Comentario al caso Wong Ho Wing vs. Perú. Sentencia de la Corte Interamericana de Derechos Humanos de 30 de junio de 2015 - Mosquera Monelos, Susana (Revista de Derecho, 2020)
Wong Ho Wing Vs. Peru case offers us the perfect opportunity to approach an applied study over the interjudicial dialogue so important for the international public law nowadays. Classic bilateralism among equal states has been progressively replaced by an interchange dialogue between domestic and international courts. Such a new relationship model has been intensively applied on the field of human rights, where the plasticity of these treaties must be adjusted to effectively protect the human rights. Wong Ho Wing v. Peru describe that academic development, this is the reason to pres-ent it as a real success of this inter-judicial dialogue method to protect human rights.
Keywords: international obligations of the state; human rights; interjudicial dialogue; extradition